Trends and characteristics of multiple births in Baoan Shenzhen: A retrospective study over a decade - Wenyi Tang; Lingyun Zou; Lingyun Zou (Frontiers Media S.A., 2022)
BackgroundShenzhen has the largest and youngest foreign population among all cities in China. The reproductive health of pregnant women from different backgrounds is a social issue that deserves attention. In the past decade, China has liberalized its population policies to stimulate population growth, and the proportion of multiple births has continued to increase.MethodThis retrospective cohort included 526,654 newborns born in Baoan, Shenzhen, from January 1, 2009, to December 31, 2019, including 515,016 singletons and 11,638 twins or triplets. Univariate regression models were used to analyze the effects of maternal sociodemographic characteristics, physiological characteristics, medical history, antenatal care and other factors associated with single vs. multiple births and to elucidate the changing trends of different factors affecting multiple births in the past 11 years. Additionally, fetal development in multiple births was analyzed by generalized linear mixed models.ResultsThe rates of pregnancy complications, preterm birth, and advanced-age pregnancy were significantly higher in the multiple birth mothers than in single birth mothers, and more multiple pregnancies were achieved through assisted reproductive technologies. The rates of adverse outcomes such as stillbirth, malformation, hypoxia, and ultralow body weight in multiple fetuses were significantly higher than that in singleton fetuses. The trend analysis from 2009 to 2019 showed that the socioeconomic status and health level of mothers with multiple births improved over time, and the risk during pregnancy generally decreased. Simultaneously, the development indicators of multiple fetuses have improved year by year, and the proportion of adverse outcomes has also decreased significantly. A low pre-natal care utilization rate was shown to be detrimental to the development of multiple fetuses. Independent risk factors for hypoxia and very low birth weight were also identified. The differences in secular trends between two birth groups were further revealed by time series models.ConclusionThis study presented a comprehensive survey of multiple pregnancies in the area with the largest population inflow in China. This study identified the factors that affect the health of multiple birth mothers and their fetuses, particularly suggesting that preterm birth rates and the use of assisted reproduction remain high. The findings provide a basis for the formulation of individualized pre-natal care, assisted reproductive guidance and healthcare policies for multiple births.